Autokorelacja przestrzenna i kriging - metodologia i wybrane zastosowania - Panak, Alicja (Spatial autocorrelation and kriging - methodology with some applications, 2006)
Recent research in spatial econometrics focus on a problem of analysing spatial interactions and spatial autocorrelation. Spatial relations are also extensively used in a geostatistical technique for Gaussian interpolation - kriging. The aim of this work is to present some testing methods for both global and local spatial autocorrelation, and to discuss some estimation and interpolation problems in spatial interferences context. Some applied examples are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 483-491